Revisiting Caspase-11 Function in Host Defense - Ng, Tessie M. (2013)
Pro-inflammatory caspases play important roles in innate immunity. Much attention has focused on caspase-1, which acts to eliminate pathogens by obliterating their replicative niches as well as alerting the host to their presence. Emerging data now sheds light on the lesser-studied pro-inflammatory caspase-11 in the combat between host and pathogen. With new tools available, researchers are now further elucidating the mechanisms by which caspase-11 contributes to host defense. Here, we review the emerging understanding of caspase-11 functions and mechanisms of activation, and discuss implications for human disease.